Oral magnesium supplementation improves glycemic control and lipid profile in children with type 1 diabetes and hypomagnesaemia. Issue 11 (March 2017) - Shahbah, Doaaa; Hassan, Tamer; Morsy, Saeed; Saadany, Hosam El; Fathy, Manar; Al-Ghobashy, Ashgan; Elsamad, Nahla; Emam, Ahmed; Elhewala, Ahmed; Ibrahim, Boshra; Gebaly, Sherief El; Sayed, Hany El; et al.
Abstract : Abstract: Dietary supplementation with magnesium (Mg) in addition to classical therapies for diabetes may help in prevention or delaying of diabetic complications. We aimed to evaluate the status of serum Mg in children with type 1 diabetes and assessing its relationship to glycemic control and lipid profile. Then evaluating the effect of oral Mg supplementation on glycemic control and lipid parameters. We included 71 children at Pediatric Endocrinology Outpatient Clinic, Zagazig University, Egypt with type 1 diabetes and assessed HBA1c, lipid profile, and serum Mg at the start of study. Patients with serum Mg level < 1.7 mg/dL were given 300 mg Mg oxide for 3 months. After that we reevaluated HBA1c, lipid profile, and serum Mg in all patients. The study included 71 patients with type 1 diabetes (32 males and 39 females); their mean age was 9.68 ± 3.99 years. The mean serum Mg level was 1.83 ± .27 mg/dL. Hypomagnesemia was detected in 28.2% study patients. Serum Mg was found to be positively correlated with high density lipoprotein, mean corpuscular volume and platelet count ( P < 0.001), and negatively correlated with age, HbA1c, triglycerides, total cholesterol, low density lipoprotein, and duration of diabetes ( P < 0.001). There was significant reduction in HBA1c in group given Mg supplementation. HBA1c was initially 10.11% ± 0.87%. After 3 months of oral Mg supplementation it is reduced to 7.88% ± 0.42% ( P < 0.001). There was statistically significant difference in lipid parameters in hypomagnesemic diabetic patients before and after Mg supplementation with significant reduction in serum triglycerides, LDL, and total cholesterol following Mg supplementation with P < 0.001. Although HDL shows a significant increase after Mg supplementation in hypomagnesemic diabetic children with P < 0.001. Correction of hypomagnesemia in type 1 diabetic children with oral Mg supplements is associated with optimization of glycemic control and reduction of atherogenic lipid fraction as well as increase in protective lipid fraction.